56 Exploring spatial patterns of pedestrian injury by age and severity in toronto, Canada. (9th June 2015) - Grise, Emily; Buliung, Ron; Rothman, Linda; Howard, Andrew
Abstract : The City of Toronto, Canada experienced a ten-year high in pedestrian fatalities last year and currently has the highest pedestrian collision rate of all Canadian cities. This research aims to explore spatial patterns of pedestrian injury in Toronto, with a particular focus on age-based differences in the geography of injury and injury risk. A Method was developed to analyse pedestrian injury event intensity throughout the city while controlling for the population at risk, to visually explore and identify geographical areas where there is a higher than expected risk of pedestrian-vehicle collisions by age. The geography of injury severity was also explored, with a view to identifying the spatial patterning of pedestrian injury by age and severity across the city. Four age categories were examined; age-group differences in the geography of injury are expected given age-related differences in activity patterns. Weekday pedestrian injury events were the focus of this study, as a result of expected differences between weekday and weekend activity patterns. Results of the spatial analysis demonstrate geographical variation in injury intensity by age group. Examining injury events by level of severity reveals that the intensity of fatal and major injury events shifts away from the downtown core towards the inner suburbs of the city, particularly for children and seniors. The findings suggest that there should be additional attention, on the policy and planning front, to pedestrian safety in the inner suburbs. Intervention planning and implementation should acknowledge spatial differences in pedestrian motor vehicle collisions by age and severity.